Enhancing the catalytic repertoire of nucleic acids. II. Simultaneous incorporation of amino and imidazolyl functionalities by two modified triphosphates during PCR - Gourlain, Thierry (Oxford University Press, 2001)
The incorporation of potentially catalytic groups into DNA is of interest for the in vitro selection of novel deoxyribozymes. We have devised synthetic routes to a series of three C7 modified 7-deaza-dATP derivatives with pendant aminopropyl, Z-aminopropenyl and aminopropynyl side chains. These modified triphosphates have been tested as substrates for Taq polymerase during PCR. All the modifications are tolerated by this enzyme, with the aminopropynyl side chain giving the best result. Most protein enzymes have more than one type of catalytic group located in their active site. By using C5-imidazolyl-modified dUTPs together with 3-(aminopropynyl)-7-deaza-dATP in place of the natural nucleotides dTTP and dATP, we have demonstrated the simultaneous incorporation of both amino and imidazolyl moieties into a DNA molecule during PCR. The PCR product containing the four natural bases was fully digested by XbaI, while PCR products containing the modified 7-deaza-dATP analogues were not cleaved. Direct evidence for the simultaneous incorporation during PCR of an imidazole-modified dUTP and an amino-modified 7-deaza-dATP has been obtained using mass spectrometry.